Infection of Escherichia coli by T2 and T4 Bacteriophages as Seen in the Electron Microscope: T4 Head Morphogenesis - Simon, Lee D. (1972)
Bacteriophage T4 capsids seem to be assembled on E. coli protoplasmic membranes. This process seems to involve “lumps” of head protein, which convert to τ particles, which in turn give rise to empty heads. The empty heads leave the bacterial membrane and are then filled with DNA in the central region of the cell. T4 gene 16 and 17 products appear to be necessary for head filling.